Efecto de la morfología y color de los huevos sobre el sexo de pollitos COBB 500 - Figueroa Zambrano, José Rafael (2024)
The objective of this research was to evaluate the effect of the morphology and color of the eggs on the sex of the COBB 500 chicks. The place of execution was within the Teaching, Research and Linkage Unit Hatchery Plant of the ESPAM-MFL. The study was carried out under a Completely Randomized Design (DCA), with a factorial arrangement (2x2) with four treatments and five repetitions. For data analysis, ADEVA was used through the InfoStat 2020 statistical package and comparison of Tukey 5% means. The variable considered was the sex of the chicks. In the results, no significant differences were found for morphology (p= 0.6569), in elongated eggs 55.38% were obtained and the rounded ones 52.94% females, while the elongated ones produced 44.07% and the rounded ones 44.62% males. Likewise, there was no significant difference for color over sex (p = 0.2679), where white eggs were produced by 51.15% and brown eggs by 57.17% of females and 42.83% of males. and 48.86% white and brown respectively. It is concluded that morphology and color have no significant effect on the sex of COBB 500 chicks.